(untitled) - David, Andrej (Doprava a spoje, 2012)
Container transport belongs to the fastest developing modes of transport in the world. Containers started to be used in sea transport due to saving of loading time of cargo in sea ports, its protection against damaging, losing or stealing. In the world there are three main container trade routes. The busiest route is between North America and Far East. About 50 % of containers are handled in the top twenty sea ports and their container terminals. Most of them are located in Asia, three of them are in Europe and three of them are situated in the USA.